Impact of DNA methylation on ADME gene expression, drug disposition, and efficacy. (3rd April 2022) - Hao, Xu; Li, Yuanyuan; Bian, Jialu; Zhang, Ying; He, Shiyu; Yu, Feng; Feng, Yufei; Huang, Lin
Abstract: Interindividual differences in drug response have always existed in clinical treatment. Genes involved in drug absorption, distribution, metabolism, and excretion (ADME) play an important role in the process of pharmacokinetics. The effects of genetic polymorphism and nuclear receptors on the expression of drug metabolism enzymes and transporters can only explain some individual differences in clinical treatment. Several key ADME genes have been demonstrated to be regulated by epigenetic mechanisms that can potentially affect inter-individual variability in medical treatment. Emerging studies have focused on the importance of DNA methylation for ADME gene expression and for drug response. Among them, the most studied are anti-tumor drugs, followed by anti-tuberculous and anti-platelet drugs. Therefore, we provide an epigenetics perspective on variability in drug response. The review summarizes the correlation between ADME gene expression and DNA methylation, including the exact methylation locations, and focuses on the corresponding drug disposition and effects to illuminate interindividual differences in clinical medication.